Existing branches correlatively inhibit further branching in Trifolium repens: possible mechanisms - Thomas, R. G. (Oxford University Press, 2011)
In Trifolium repens removal of any number of existing branches distal to a nodal root stimulates development of axillary buds further along the stem such that the complement of branches distal to a nodal root remains constant. This study aimed to assess possible mechanisms by which existing branches correlatively inhibit the outgrowth of axillary buds distal to them. Treatments were applied to basal branches to evaluate the roles of three postulated inhibitory mechanisms: (I) the transport of a phloem-mobile inhibitory feedback signal from branches into the main stem; (II) the polar flow of auxin from branches into the main stem acting to limit further branch development; or (III) the basal branches functioning as sinks for a net root-derived stimulatory signal (NRS). Results showed that transport of auxin, or of a non-auxin phloem-mobile signal, from basal branches did not influence regulation of correlative inhibition and were consistent with the possibility that the intra-plant distribution of NRS could be involved in the correlative inhibition of distal buds by basal branches. This study supports existing evidence that regulation of branching in T. repens is dominated by a root-derived stimulatory signal, initially distributed via the xylem, the characterization of which will progress the generic understanding of branching regulation.